316 Magnetic Resonance Imaging Analysis of the Combined AOSpine North America and International Studies, Part I: The Prevalence and Spectrum of Pathologies in a Global Cohort of Patients With Degenerative Cervical Myelopathy. (1st August 2016) - Nouri, Aria; Martin, Allan R.; Tetreault, Lindsay; Nater, Anick; Kato, So; Nakashima, Hiroaki; Nagoshi, Narihito; Reihani-Kermani, Hamed; Fehlings, Michael G.
Abstract: INTRODUCTION: Degenerative cervical myelopathy (DCM) encompasses a spectrum of age-related conditions that result in progressive spinal cord injury through static and dynamic injury mechanisms. Through detailed review of MRIs from prospective AOSpine multicenter studies, the global prevalence of degenerative cervical pathologies of surgically treated DCM patients is reported. METHODS: MRIs of 458 patients were obtained from North America (n = 197), Europe (n = 92), Latin America (n = 57), and Asia-Pacific (n = 112) and assessed for the type of pathology, source of stenosis, level of maximum cord compression, levels of spinal cord compression (SCC), presence of signal changes on T2-weighted images (T2WI) and T1-weighted images, and the levels of T2WI signal change. The proportion of degenerative changes present alongside other diagnoses was computed as well as the prevalence of pathologies per geographical region. The prevalence of degenerative changes was separated by sex and assessed using χ 2 analysis. RESULTS: Spondylosis was the most frequent cause of SCC (89.7%) and it was frequently accompanied by enlargement of the ligamentum flavum (59.85%). Ossification of the posterior longitudinal ligament (OPLL) was accompanied by spondylosis in 91.7%. Single-level disc pathology, OPLL, and spondylolisthesis had a prevalence of ∼10%. Klippel-Feil syndrome was observed in 2.8%. Single-level pathology was less common in North America, and OPLL was more common and spondylolisthesis less common in Asia-Pacific. Females presented more commonly with single-level disc pathology ( P = .013), and males with spondylosis ( P = .017) and enlargement of ligamentum flavum ( P = .012). Globally, C5-6 was the most frequent maximum compressed site (39.7%) and region for T2WI hyperintensity (38.9%). T2WI hyperintensity more commonly presented in males ( P < .001). CONCLUSION: DCM pathologies, including OPLL, are highly interrelated and rarely present in isolation. Females presented with milder evidence of DCM on MRI. There are also variances in the spectrum and prevalence of pathologies between geographical regions and these may be due to a multitude of causes.